Stress, coping and adherence to immunosuppressive medications in kidney transplantation: a comparative study - Brito, Daniela Cristina Sampaio de; Marsicano, Elisa Oliveira; Grincenkov, Fabiane Rossi dos Santos; Colugnat, Fernando Antônio Basile; Lucchetti, Giancarlo; Sanders-Pinheiro, Helady (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Adherence to medication is a key issue relating to outcomes from transplantation and it is influenced by several factors, such as stress and coping strategies. However, these factors have been poorly explored. We aimed to compare stress and coping strategies between adherent and nonadherent renal transplant recipients who were receiving immunosuppression. DESIGN AND SETTING: We conducted a comparative, cross-sectional and observational study at a university-based transplantation clinic in Juiz de Fora, Brazil. METHODS: Fifty patients were recruited and classified as adherent or nonadherent following administration of the Basel Assessment of Adherence to Immunosuppressive Medications Scale. Stress was evaluated using the Lipp Stress Symptom Inventory for Adults and coping strategies were assessed using the Ways of Coping Scale. RESULTS: The study included 25 nonadherent patients and 25 controls with a mean age of 44.1 ± 12.8 years and median post-transplantation time of 71.8 months. Stress was present in 50% of the patients. Through simple logistic regression, nonadherence was correlated with palliative coping (OR 3.4; CI: 1.02- 11.47; P < 0.05) and had a marginal trend toward significance with more advanced phases of stress (OR 4.7; CI: 0.99-22.51; P = 0.053). CONCLUSION: Stress and coping strategies may have implications for understanding and managing nonadherent behavior among transplantation patients and should be considered among the strategies for reducing nonadherence.